The Role of Lavender Essential Oils (LEO) in Managing Stress and Neuroinflammation: An Immunopsychiatric Perspective - Kamila, Putri Faradisa; Algristian, Hafid (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2025)
Lavender essential oil (LEO) has gained significant attention for its potential role in managing stress and neuroinflammation, offering a promising avenue in immunopsychiatry. Rich in bioactive compounds such as linalool and linalyl acetate, LEO exhibits anxiolytic, anti- inflammatory, and neuroprotective properties. Emerging evidence suggests that LEO modulates the hypothalamic-pituitary-adrenal (HPA) axis, reduces cortisol levels, and influences neurotransmitter pathways, thereby alleviating stress-related symptoms. Furthermore, its anti- inflammatory effects contribute to mitigating neuroinflammation, a key factor in mood disorders such as depression and anxiety. This review explores the immunopsychiatric mechanisms underlying LEO’s therapeutic potential, highlighting its role as a complementary intervention in stress-related neuropsychiatric conditions.